Aesthetic surgical crown lengthening on teeth 11 and 21 - Saptaningrum, Mardikaning Riasta; Wahjuningrum, Dian Agustin; Sampoerno, Galih; Prasetyo, Eric Priyo; Handoko, Jessica Cristy; Chang, Nicole Ava; Ismiyatin, Kun (Universitas Airlangga, 2024)
Background: In dental treatment planning, aesthetic considerations are crucial due to the relationship between a smile and facial beauty. Crown lengthening is a procedure used to achieve aesthetic smiles, particularly in cases of subgingival caries, fractures, and short clinical crowns. Purpose: The purpose of this case report is to achieve aesthetic improvement of the central incisors through crown lengthening procedures. Case: A 31-year-old female patient presented with a complaint of a broken upper left front tooth and easily bleeding gums. Clinical examination revealed Ellis class 1 fracture at the incisal-distal of tooth 21. The patient exhibited poor oral hygiene with visible calculus on upper and lower jaw teeth. There was gingival hyperplasia, redness, bleeding tendency, and the gingival margin height of teeth 11 and 21 appeared lower than teeth 12 and 22. Radiographically, the alveolar crest was distant from the CEJ. Case Management: Treatment plan included crown lengthening on teeth 11 and 21 with composite restoration on tooth 21. Crown lengthening, a surgical procedure designed to increase the extent of supragingival tooth structure for restorative or aesthetic purposes by repositioning the gingival margin apically was performed. This procedure is indicated for teeth with subgingival caries, extensive caries shortening the tooth, fractures, and short clinical crowns. Conclusion: Crown lengthening should consider the biological width to prevent bone resorption, gingival recession, inflammation, or hypertrophy. When performed under ideal clinical conditions, crown lengthening provides satisfactory outcomes both functionally and aesthetically.